A Performance Evaluation of RPC, Java RMI, MPI and PVM - Qureshi, Kalim; Rashid, Haroon (Malaysian Journal of Computer Science, 2005)
This paper presents performance comparison of Remote Procedure Calls (RPC), Java Remote Machine Invocation (RMI), Message Passing Interface (MPI) and Parallel Virtual Machine (PVM). The Bandwidth, latency and parallel processing time are measured using standard benchmarks. The results show that the MPI performance is much closer to RPC performance.